2018
DOI: 10.1155/2018/2750632
|View full text |Cite
|
Sign up to set email alerts
|

Visual-Evoked-Response-Supported Outcome of Intravitreal Erythropoietin in Management of Indirect Traumatic Optic Neuropathy

Abstract: Purpose Investigating the efficacy of intravitreal injection of erythropoietin (EPO) in managing indirect traumatic optic neuropathy (ITON) of different durations. Methods A case series that included two groups of ITON patients: recent ITON group (<3 months trauma duration; 7 eyes) and old duration ITON group (3–36 months; 7 eyes). Diagnostic computerized tomography (CT) and baseline flash visual evoked response (VER) were performed at the presentation time. At the initial visit and each follow-up, all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In present study, mean VEP amplitude as well as latency significantly improved following treatment (p<0.05). These findings were similar to study by Rashad et al, 9 in which significant improvement was found in BCVA, VER amplitude, and latency (P < 0.0001, 0.0154, and 0.0291, respectively) even after 1 injection of steroid.…”
Section: Discussionsupporting
confidence: 92%
“…In present study, mean VEP amplitude as well as latency significantly improved following treatment (p<0.05). These findings were similar to study by Rashad et al, 9 in which significant improvement was found in BCVA, VER amplitude, and latency (P < 0.0001, 0.0154, and 0.0291, respectively) even after 1 injection of steroid.…”
Section: Discussionsupporting
confidence: 92%
“…These promising results of our study are in accordance with previously published studies. For instance, some studies have successfully used EPO in the treatment of indirect traumatic ON at such doses, ranging from 2000 IU (intravitreal) to 10000 IU (intravenous) twice daily for 3 days or even higher doses [23,24]. In a prospective and noncomparative study, 16 cases with methanol ON were included.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have successfully used erythropoietin in the management of optic neuropathy due to methanol poisoning [11][12][13][14][15][16] at such doses, ranging from 2000 IU (intravitreal) to 10000 IU (intravenous) twice daily for three days [15,21]. Conversely, in most previous studies, erythropoietin were injected (intravenous or intravitreal) with or without corticosteroid in the management of optic neuropathy due to methanol poisoning and also, erythropoietin were injected at high dosages but in fewer repeats [17,20].…”
Section: Discussionmentioning
confidence: 99%